Interferon lambda 4 impairs hepatitis C viral antigen presentation and attenuates T cell responses - Chen, Qian; Coto-Llerena, Mairene; Suslov, Aleksei; Teixeira, Raphael Dias; Fofana, Isabel; Nuciforo, Sandro; Hofmann, Maike; Thimme, Robert; Hensel, Nina; Lohmann, Volker; Ng, Charlotte K. Y.; Rosenberger, George; et al. (Nature Communications, 2021)
Genetic variants of the interferon lambda (IFNL) gene locus are strongly associated with spontaneous and IFN treatment-induced clearance of hepatitis C virus (HCV) infections. Individuals with the ancestral IFNL4-dG allele are not able to clear HCV in the acute phase and have more than a 90% probability to develop chronic hepatitis C (CHC). Paradoxically, the IFNL4-dG allele encodes a fully functional IFNλ4 protein with antiviral activity against HCV. Here we describe an effect of IFNλ4 on HCV antigen presentation. Only minor amounts of IFNλ4 are secreted, because the protein is largely retained in the endoplasmic reticulum (ER) where it induces ER stress. Stressed cells are significantly weaker activators of HCV specific CD8+ T cells than unstressed cells. This is not due to reduced MHC I surface presentation or extracellular IFNλ4 effects, since T cell responses are restored by exogenous loading of MHC with HCV antigens. Rather, IFNλ4 induced ER stress impairs HCV antigen processing and/or loading onto the MHC I complex. Our results provide a potential explanation for the IFNλ4-HCV paradox.